2021
DOI: 10.21037/jgo-21-247
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microvessel density (MVD) and multi-spiral CT (MSCT) perfusion parameters of esophageal cancer lesions and the diagnostic value of combined CtBP2 and P16INK4A

Abstract: Background: This article aims to analyze the correlation between microvessel density (MVD) and multispiral CT(MSCT) perfusion parameters of esophageal cancer lesions, and the diagnostic value of combining C-terminal binding protein 2 (CtBP2) and P16 inhibitor of cyclin-dependent kinase 4a (P16 INK4A ). Methods: A total of 42 cases of normal esophageal mucosa tissues >5 cm from the cancer tissue were selected as the control group. The expression levels of CtBP2 and P16 INK4A and the values of MSCT perfusion par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In our study, we utilized MSCT perfusion imaging to assess its diagnostic potential. The elderly SAP patients in our study exhibited typical radiological features during the MSCT perfusion imaging process, consistent with prior reports from domestic and international sources [ 22 ]. In our study, the incidence of peripancreatic infection was 20.91%, with one patient succumbing to it, resulting in a mortality rate of 0.91%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we utilized MSCT perfusion imaging to assess its diagnostic potential. The elderly SAP patients in our study exhibited typical radiological features during the MSCT perfusion imaging process, consistent with prior reports from domestic and international sources [ 22 ]. In our study, the incidence of peripancreatic infection was 20.91%, with one patient succumbing to it, resulting in a mortality rate of 0.91%.…”
Section: Discussionsupporting
confidence: 90%
“…MSCT perfusion imaging is an advanced technique that relies on contrast agent diffusion principles and mathematical modeling to calculate perfusion parameters [ 22 ]. It assesses tissue perfusion by quantifying the difference between arterial inflow and venous outflow rates in terms of contrast agent accumulation in tissues and organs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique was studied in solid tumors of the kidney, pancreas, liver, head and neck, and lung, the results showed a positive correlation between vascular parameters and MVD [12][13][14]. However, the use of CT energy spectroscopy and perfusion imaging in colorectal cancer is relatively rare, some of the studies were also only limited to the correlation between CT-related vascular parameters and MVD [15], The diagnostic value of using CT-related vascular parameters for high and low MVD techniques was less well studied. Therefore, in this study, we systematically analyzed the diagnostic value of CT energy spectrum and perfusion parameters for colorectal cancer with different microvessel densities.…”
Section: Discussionmentioning
confidence: 99%
“…CTPI can be used to evaluate the perfusion and vascularity of lesions in the lung and many other organs. [21][22][23][24][25][26][27][28] Wang et al 21 reported that parameters of CTPI (including BF, BV and PS but not MTT) of SPNs were significantly correlated with SPNs' microvessel density (MVD) and luminal vascular parameters such as luminal vascular number (LVN), luminal vascular area (LVA), and luminal vascular perimeter (LVP). Huang et al 22 analyzed the CT perfusion parameters (BF, BV, MTT, and PS) and the microvessel parameters (MVD, LVN, LVA, and LVP) in the non-small cell lung cancer (NSCLC) patients with and without lymph node metastasis.…”
Section: Ctpi In Evaluating Spnsmentioning
confidence: 99%